3e(adsbygoogle = window.adsbygoogle || []).push({}); ^{3y-6}= 2x^{2}-1

ln3e^{3y-6}=ln2x^{2}-lne

ln3e^{3y-6}=ln2x^{2}/lne

3e^{3y-6}=2x^{2}/e

3e^{3y-6}*e=2x^{2}

e^{3y-6}=(2/3)x^{2}

3y-6=ln((2/3)x^{2})

3y=ln((2/3)x^{2})+6

y=(1/3)ln((2/3)x^{2})+2

I wonder the answer is correct, the question is asking about the equation of y.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Logarithmic equations help

**Physics Forums | Science Articles, Homework Help, Discussion**